Direct composite restoration of permanent anterior teeth uncomplicated crown fractures - Nicholas, Ashley Evans; Andang, Milly Armilia; Hidayat, Opik Taofik (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2012)
An uncomplicated crown fracture is a fracture that involves only the tooth enamel or the dentin and tooth enamel without any damage or exposure to the pulp. Crown fracture of the anterior teeth usually caused by traumatic forces such as falls, accidents, violence, or sports activities. Traumatic injuries of the oral region frequently involve the anterior teeth, especially maxillary incisors due to the anatomic factors which may affect the functional and aesthetical values of the teeth. The objective of this literature study was to know more about uncomplicated crown fracture of the anterior teeth and its restoration. This research was a literature study performed by researching, highlighting various interesting facts and compiling the relevant published journals. The most common and ideal direct restoration of the anterior teeth was the composite resin restoration. The anterior teeth restoration was considered to be a complex and challenging case to solves due to the fact that besides reconstructing the tooth and regaining the function, the aesthetical aspect was also becoming the main objectives. The permanent anterior teeth uncomplicated crown fracture was the most common case of tooth fractures which was mainly caused by traumatic injuries such as falls, accidents, excessive forces, violence, and also sports activities. Dental injuries of the anterior teeth also affected the aesthetical properties and the function of the tooth. Composite resin restoration was able to performed directly on the permanent anterior teeth uncomplicated crown fracture.